Solid electrolyte material, solid electrolyte, all-solid secondary battery, and method for producing solid electrolyte material
The development of a solid electrolyte material with a specific composition and cation ratio addresses the low ionic conductivity issue in existing materials, enhancing performance and safety by preventing hydrogen sulfide generation in all-solid secondary batteries.
Patent Information
- Application Number
- JP2021021800
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-15
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-02-15
AI Technical Summary
Existing solid electrolyte materials for all-solid secondary batteries have low ionic conductivity, particularly those without sulfur that could generate hydrogen sulfide.
A solid electrolyte material with a composition represented by the general formula (Li)3-xM1x)Y(M21 6-yM22 y), where M1 is an alkali metal other than lithium, M2 is a halogen, and x and y are within specific ranges, is developed. This material has a cation ratio of M1/(Li+M1) greater than 0 and less than 0.07, enhancing ionic conductivity.
The proposed solid electrolyte material achieves significantly improved ionic conductivity, preventing hydrogen sulfide generation and making it suitable for practical applications in all-solid secondary batteries.
Smart Images

Figure 0007670499000007 
Figure 0007670499000008 
Figure 0007670499000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid electrolyte material for an all-solid-state secondary battery, a solid electrolyte, and an all-solid-state secondary battery using the same. [Background technology]
[0002] As a sulfur-free solid electrolyte material that may generate hydrogen sulfide, the use of a solid electrolyte material containing a halogen component instead of a sulfide has been considered (Patent Document 1).
[0003] However, the solid electrolyte material described in Patent Document 1 has an ionic conductivity of 10 -4 The ionic conductivity is low at only S / cm, and it is necessary to further improve it for practical use. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 025582 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in view of the above problems, and has as its main object to provide a solid electrolyte material that does not generate hydrogen sulfide and has high ionic conductivity. [Means for solving the problem]
[0006] The present invention was completed only after the inventors realized, as a result of intensive research, that the ionic conductivity of a halogen-containing solid electrolyte material can be greatly improved compared to conventional solid electrolyte materials by containing lithium and yttrium and further containing an alkali metal element other than lithium. That is, the solid electrolyte material according to the present invention has a composition represented by the following general formula (Chemical Formula 1), and is characterized in that the cation ratio (M1 / Li+M1), which is the content ratio of the M1 element to the total amount of the Li element and the M1 element in the general formula, is greater than 0 and is 0.07 or less.
[0007] [ka] (The M1 element in the formula includes at least one selected from the group consisting of Na, K, Rb, Cs, and Fr. The M2 element in the formula includes at least one selected from the group consisting of Cl, Br, I, and F. x in the formula is greater than 0 and less than 3.)
[0008] The solid electrolyte thus constructed does not contain sulfur, which may generate hydrogen sulfide, and can achieve a significantly improved ionic conductivity compared to conventional solid electrolytes.
[0009] The solid electrolyte material has peaks at least at 2θ=27.72°±0.50°, 31.90°±0.50°, 46.34°±0.50°, 55.09°±0.50°, and 57.39°±0.50° in X-ray diffraction measurement using CuKα radiation.
[0010] The value of x in the above formula is preferably greater than 0 and equal to or less than 0.21.
[0011] The M1 element is preferably Na and / or K.
[0012] The M2 element is preferably Cl and / or Br, and more preferably Cl and Br.
[0013] A step of mechanically milling a mixture of LiM2, YM2 and M1M2 in a predetermined ratio to obtain glass; and heat-treating the glass at a temperature equal to or higher than the glass transition temperature to obtain a glass ceramic having a composition represented by the following general formula (Chemical Formula 2), in which a cation ratio (M1 / Li+M1), which is the content ratio of M1 element to the total amount of Li element and M1 element in the general formula, is greater than 0 and is 0.07 or less.
[0014] [ka] (The M1 element in the formula includes at least one selected from the group consisting of Na, K, Rb, Cs, and Fr. The M2 element in the formula includes at least one selected from the group consisting of Cl, Br, I, and F. x in the formula is greater than 0 and less than 3.) Effect of the Invention
[0015] According to the present invention, it is possible to provide a solid electrolyte material that does not generate hydrogen sulfide and has high ionic conductivity. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic diagram showing the structure of an all-solid-state secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing X-ray diffraction patterns of solid electrolyte materials according to examples and comparative examples of the present invention. [Diagram 3] FIG. 2 is a diagram showing an X-ray diffraction pattern of a solid electrolyte material according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0018] The solid electrolyte material according to this embodiment is used as a solid electrolyte in, for example, an all-solid-state lithium secondary battery 1 as shown in FIG.
[0019] <1. Structure of all-solid-state lithium-ion secondary battery 1> As shown in FIG. 1, the all-solid-state lithium secondary battery 1 has a structure in which a positive electrode layer 10, a negative electrode layer 20, and a solid electrolyte layer 30 located between the positive electrode layer 10 and the negative electrode layer 20 are laminated.
[0020] (1.1. Positive electrode layer 10) The positive electrode layer 10 includes a positive electrode active material and a solid electrolyte. The solid electrolyte will be described later in connection with the solid electrolyte layer 30.
[0021] The positive electrode active material may be any material capable of reversibly absorbing and releasing lithium ions.
[0022] For example, the positive electrode active material can be formed using lithium salts such as lithium cobalt oxide (hereinafter referred to as LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (hereinafter referred to as NCA), lithium nickel cobalt manganate (hereinafter referred to as NCM), lithium manganate, lithium iron phosphate, nickel sulfide, copper sulfide, lithium sulfide, sulfur, iron oxide, vanadium oxide, etc. These positive electrode active materials may be used alone or in combination of two or more.
[0023] Further, the positive electrode active material is preferably formed by including a lithium salt of a transition metal oxide having a layered rock salt structure among the above-described lithium salts. Here, the "layered rock salt structure" is a structure in which oxygen atom layers and metal atom layers are alternately and regularly arranged in the <111> direction of the cubic rock salt structure, and as a result, each atom layer forms a two-dimensional plane. The "cubic rock salt structure" represents a sodium chloride type structure which is a type of crystal structure. Specifically, it represents a structure in which the face-centered cubic lattices formed by each of the cations and anions are arranged so as to be shifted from each other by 1 / 2 of the edge of the unit lattice.
[0024] Examples of the lithium salt of the transition metal oxide having such a layered rock salt structure include, for example, LiNi a Co b Al c O 2 (NCA), or LiNi a Co b Mn c O 2 (NCM) (where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1), and lithium salts of ternary system transition metal oxides such as these can be mentioned.
[0025] In addition to those described above, the positive electrode layer 10 may contain a conductive assistant, a binder, a filler, a dispersant, an ion conductive assistant, etc. Examples of the conductive assistant that can be blended in the positive electrode layer 10 include, for example, graphite, carbon black, acetylene black, ketjen black, carbon fiber, metal powder, etc. Examples of the binder that can be blended in the positive electrode layer 10 include, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc. Furthermore, as the filler, dispersant, ion conductive assistant, etc. that can be blended in the positive electrode layer 10, known materials generally used for electrodes of all-solid-state lithium ion secondary batteries can be used.
[0026] The all-solid-state lithium-ion secondary battery 1 may further include a positive electrode current collector that supplies a current to the positive electrode layer 10. The positive electrode current collector is disposed on the outside of the positive electrode layer 10. As the positive electrode current collector, for example, a plate-shaped or foil-shaped body made of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof can be used.
[0027] (1.2. Negative Electrode Layer 20) The negative electrode layer 20 includes a negative electrode active material and a solid electrolyte. The solid electrolyte will be described later in connection with the solid electrolyte layer 30.
[0028] The negative electrode active material has a lower charge / discharge potential than the positive electrode active material, and is made of a negative electrode active material that can be alloyed with lithium or can reversibly absorb and release lithium.
[0029] The negative electrode active material may be, for example, a metal active material or a carbon active material. Examples of the metal active material include metals such as lithium (Li), indium (In), aluminum (Al), tin (Sn), and silicon (Si), and alloys of these metals. Examples of the carbon active material include artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, non-graphitizable carbon, etc. These negative electrode active materials may be used alone or in combination of two or more.
[0030] In addition to the above-mentioned negative electrode active material and solid electrolyte, the negative electrode layer 20 may contain additives such as a conductive agent, a binder, a filler, a dispersant, or an ion conductive agent as appropriate.
[0031] The additives to be blended in the negative electrode layer 20 may be the same as those blended in the positive electrode layer 10 described above.
[0032] The all-solid-state lithium-ion secondary battery 1 may further include a negative electrode current collector that supplies a current to the negative electrode layer 20. The negative electrode current collector is disposed on the outside of the negative electrode layer 20. The negative electrode current collector is preferably made of a material that does not react with lithium, that is, does not form any alloy or compound. Examples of materials that constitute the negative electrode current collector include copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), and nickel (Ni). The negative electrode current collector may be made of any one of these metals, or may be made of an alloy or clad material of two or more metals.
[0033] (1.3.Solid electrolyte layer 30) The solid electrolyte layer 30 is a layer formed between the positive electrode layer 10 and the negative electrode layer 20, and contains a solid electrolyte.
[0034] The solid electrolyte layer 30 may further include a binder. Examples of the binder included in the solid electrolyte layer 30 include styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, and polyethylene.
[0035] (1.3.1. Solid electrolytes and solid electrolyte materials) The solid electrolyte is, for example, a powder made of a solid electrolyte material. The solid electrolyte material does not contain sulfur, but contains a halogen element, lithium element, yttrium element, and an alkali metal other than lithium, and is represented by the following chemical formula.
[0036] [ka] (The M1 element in the formula includes at least one selected from the group consisting of Na, K, Rb, Cs, and Fr. The M2 element in the formula includes at least one selected from the group consisting of Cl, Br, I, and F. x in the formula is greater than 0 and less than 3.)
[0037] The M1 element in the above chemical formula may contain one or more elements selected from the group consisting of Na, K, Rb, Cs and Fr, and preferably contains Na and / or K.
[0038] The M2 element in the formula may contain at least one or more elements selected from the group consisting of Cl, Br, I and F, but is preferably Cl and / or Br, and is particularly preferably a combination of Cl and Br. When Cl and Br are used in combination, the contents of Cl and Br in the M2 element may be equal to each other or different.
[0039] In the formula, x need not be zero, and it is preferable that x is greater than 0 and equal to or less than 0.21.
[0040] In the above chemical formula, the cation ratio (M1 / Li+M1) representing the content ratio of M1 element to the total amount of lithium element and M1 element is more than 0 and 0.07 or less. The cation ratio is preferably 0.04 or less, and particularly preferably 0.02 or less. In this embodiment, the cation ratio is a molar ratio.
[0041] The solid electrolyte material represented by the above chemical formula has peaks at positions of at least 2θ = 27.72° ± 0.50°, 31.9°6 ± 0.50°, 46.34° ± 0.50°, 55.19° ± 0.50° and 57.39° ± 0.50° in the X-ray diffraction measurement using CuKα rays.
[0042] As specific examples of the solid electrolyte material described above, for example, (Li 3-x M1 x )Y(Cl 6-y Br y )(0 < x ≤ 0.2, 2 ≤ y), (Li 3-x M1 x )YCl 3 Br 3 (0 < x ≤ 0.2), (Li 3-x M1 x )YBr 6 (0 < x ≤ 0.2), etc. can be mentioned. More specifically, for example, (Li 2.9875 M1 0.0125 )YCl 3 Br 3 , (Li 2.975 M1 0.025 )YCl 3 Br 3 , (Li 2.95 M1 0.05 )YCl 3 Br 3 , (Li 2.9 M1 0.1 )YCl 3 Br 3 , (Li 2.8 M1 0.2 )YCl 3 Br 3 , etc. can be mentioned.
[0043] Next, a method for manufacturing an all-solid-state lithium-ion secondary battery including the above-described solid electrolyte material and a solid electrolyte containing this solid electrolyte material will be described. <2. Manufacturing Method of All-Solid-State Lithium-Ion Secondary Battery 1> The all-solid-state lithium-ion secondary battery 1 can be manufactured by fabricating a positive electrode layer 10, a negative electrode layer 20, and a solid electrolyte layer 30 and then laminating these layers. Hereinafter, each step will be described in detail.
[0044] (2.1. Process for Producing Positive Electrode Layer 10) The method for producing the positive electrode layer 10 is not particularly limited, but it can be produced, for example, by the following steps.
[0045] Materials constituting the positive electrode layer 10 (positive electrode active material, binder, etc.) are added to a non-polar solvent to prepare a slurry (the slurry may be a paste, and the same applies to other slurries). The obtained slurry is then applied onto a positive electrode current collector and dried. The obtained laminate is then pressed (for example, pressed using hydrostatic pressure) to prepare the positive electrode layer 10. The pressing step may be omitted. The positive electrode layer 10 may be prepared by compacting a mixture of materials constituting the positive electrode layer 10 into a pellet shape or by stretching it into a sheet shape. When preparing the positive electrode layer 10 by these methods, the positive electrode current collector may be omitted.
[0046] (2.2. Preparation of negative electrode layer 20) The method for producing the negative electrode layer 20 is not particularly limited, and the negative electrode layer 20 can be produced, for example, by the following production method.
[0047] When a lithium-containing metal foil is used as the negative electrode active material, the negative electrode layer 20 can be produced, for example, by stacking a lithium-containing metal foil, such as a lithium metal foil, on a negative electrode current collector and applying pressure.
[0048] When using a negative electrode active material other than lithium metal foil, for example, materials constituting the negative electrode layer 20 (negative electrode active material particles, solid electrolyte, binder, etc.) are added to a polar solvent or a non-polar solvent to prepare a slurry. The obtained slurry is then applied onto a negative electrode current collector and dried. The obtained laminate is then pressed (for example, pressed using hydrostatic pressure) to prepare the negative electrode layer 20. The pressing step may be omitted. The negative electrode layer 20 may also be prepared by pressing a mixture of materials constituting the negative electrode layer 20.
[0049] (2.3. Process for Producing Solid Electrolyte Layer 30) The solid electrolyte layer 30 can be made of a solid electrolyte made of the above-mentioned solid electrolyte material.
[0050] (2.3.1. Method for manufacturing solid electrolyte material) The above-mentioned solid electrolyte material can be produced by the following procedures and steps.
[0051] The raw materials LiM2, YM2, and M1M2 are each mixed to obtain the final composition of the target composition, e.g., (Li 3-x M1 x )Y(M21 6-y M22 y ) (where x is greater than 0 and less than 3). Here, M21 and M22 are elements contained in M2 and are different from each other. In this example, two elements, M21 and M22, are used as the M2 element, but the M2 element may be composed of one element or may be composed of three or more elements.
[0052] The mixture is mechanically milled, for example, with a planetary ball to obtain glass. This mechanical milling is preferably performed under the conditions of 50 rpm to 600 rpm, 0.1 hr to 50 hr, and 1 kWh to 100 kWh / kg of raw material mixture. The raw materials contained in the mixture react with each other to produce powdered glass.
[0053] Next, the glass is heat-treated to generate microcrystals, and glass ceramics, which are an aggregate of these microcrystals, are obtained. This heat treatment is performed, for example, using an electric furnace or the like, at a temperature equal to or higher than the glass transition temperature of the glass obtained by the mechanical milling treatment described above. Specifically, it is preferable to gradually increase the temperature in the electric furnace from room temperature to a target temperature equal to or higher than the glass transition temperature, and after reaching the target temperature, maintain the temperature for a certain period of time, and then gradually decrease the temperature back to room temperature. The target temperature can be appropriately changed according to the glass transition temperature of the glass to be heat-treated, but is preferably, for example, 400°C or higher and 1000°C or lower. The time for which the temperature is maintained after reaching the target temperature is preferably, for example, 1 hour or higher and 20 hours or lower. The glass ceramic thus obtained is used as a solid electrolyte material.
[0054] Specifically, the solid electrolyte layer 30 can be manufactured by forming the solid electrolyte into a film using a known film forming method such as an aerosol deposition method, a cold spray method, or a sputtering method. The solid electrolyte layer 30 may be manufactured by pressing the solid electrolyte particles alone without suspending them in a solvent or the like. The solid electrolyte layer 30 may also be manufactured by mixing the solid electrolyte, a solvent, and a binder, applying a coating, drying, and applying pressure.
[0055] (2.4. Lamination of each layer) The positive electrode layer 10, the negative electrode layer 20, and the solid electrolyte layer 30 obtained as described above are stacked such that the solid electrolyte layer 30 is located between the positive electrode layer 10 and the negative electrode layer 20, and the stacked layers are pressed in the stacking direction, whereby the all-solid-state lithium-ion secondary battery 1 can be manufactured.
[0056] <3. Effects of this embodiment> According to the solid electrolyte material according to this embodiment, it is possible to provide a solid electrolyte material that does not generate hydrogen sulfide and has high ionic conductivity. By using this solid electrolyte material as the solid electrolyte, it is possible to improve the ionic conductivity of the solid electrolyte layer in the all-solid-state lithium-ion secondary battery 1, which is completely free of the risk of generating hydrogen sulfide, compared to conventional methods.
[0057] The present invention is not limited to the above-described embodiments. For example, in the above embodiment, the solid electrolyte is described as being made of a solid electrolyte material, but the solid electrolyte may contain a solid electrolyte material, and may contain a component other than the solid electrolyte material.
[0058] In the above embodiment, the case where the solid electrolyte material is used as a solid electrolyte in an all-solid-state lithium ion secondary battery has been specifically described. However, the solid electrolyte material according to the present invention can also be used in all-solid-state batteries other than all-solid-state lithium ion secondary batteries. In addition, various modifications and combinations of the embodiments may be made as long as they do not go against the spirit of the present invention. EXAMPLES
[0059] Next, examples of the present embodiment will be described, but the present invention is not limited to only the following examples. In this example, a plurality of types of solid electrolyte materials having different compositions were prepared, and the X-ray crystal diffraction and ionic conductivity were measured for each of the prepared solid electrolyte materials.
[0060] <Example 1> First, the reagents LiBr and YCl 3 , NaBr, and the target composition (Li 2.9875 Na 0.0125 )YCl 3 Br 3 After weighing out the mixture so that the total weight of the mixture was 100g, the mixture was mixed for 20 hours in a planetary ball mill, and mechanical milling was performed at room temperature under an argon atmosphere at a rotation speed of 380 rpm for 20 hours. The (Li 2.9875 Na 0.0125 )YCl3 Br 3 A powder sample of the composition was covered with gold foil and then placed in a carbon crucible. This carbon crucible was vacuum sealed in a quartz glass tube, and the powder sample was then heat-treated using an electric furnace. The temperature inside the electric furnace was raised from room temperature to 550°C at a rate of 1.0°C / min, and the sample was heat-treated at 550°C for 12 hours. The temperature inside the furnace was then lowered from 550°C at a rate of 1.0°C / min, and the sample was cooled to room temperature to obtain the sample.
[0061] The collected sample was crushed in an agate mortar, and X-ray powder diffraction was performed to confirm that the target halide crystals were formed (Figure 2). For the X-ray powder diffraction, a multipurpose high-power X-ray diffractometer SmartLab 9Kw manufactured by Rigaku Corporation was used. The target of the X-ray tube was Cu, and measurements were performed from 2θ = 5 degrees to 90 degrees at 0.01 degree intervals.
[0062] The ionic conductivity of the obtained material was measured by the following method. The sample was crushed in an agate mortar and then pressed (pressure 400 MPa / cm 2 ) to prepare a pellet. Indium foil (500 μm thick) was attached to both sides of the pellet to prepare a pellet for ionic conductivity measurement. AC impedance measurements were performed in the frequency range of 100 mHz to 1 MHz using an AUTOLAB PGSTAT30 manufactured by Metrohm Autolab. For temperature variable tests, an ESPEC TH-241 thermostatic chamber manufactured by Espec was used, and measurements were performed in 10 degree increments from -20°C to 80°C. The ionic conductivity at room temperature obtained by this measurement method was 2.7×10 -3 S / cm was shown.
[0063] <Example 2> A solid electrolyte material was prepared using the same method as in Example 1. The target composition of the solid electrolyte material in Example 2 was (Li 2.975 Na 0.025 )YCl 3 Br 3The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 2. From the results in Figure 2, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 3.4 × 10 at 25 °C. -3 S / cm.
[0064] <Example 3> A solid electrolyte material was prepared using the same method as in Example 1. The target composition was (Li 2.95 Na 0.05 )YCl 3 Br 3 The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 2. From the results in Figure 2, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 2.9 × 10 at 25 °C. -3 S / cm.
[0065] <Example 4> A solid electrolyte material was prepared using the same method as in Example 1. The target composition was (Li 2.9 Na 0.1 )YCl 3 Br 3 The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 2. From the results in Figure 2, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 2.8 × 10 at 25 °C. -3 It was S / cm.
[0066] <Example 5> A solid electrolyte material was prepared using the same method as in Example 1. The target composition was (Li 2.8 Na 0.2 )YCl 3 Br 3The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 2. From the results in Figure 2, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 2.2 × 10 at 25 °C. -3 It was S / cm.
[0067] <Example 6> A solid electrolyte material was prepared using the same method as in Example 1. The target composition was (Li 2.96 Na 0.04 )YCl 3 Br 3 The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 2. From the results in Figure 2, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 3.0×10 at 25°C. -3 It was S / cm.
[0068] <Example 7> A solid electrolyte material was prepared using the same method as in Example 1. The target composition was (Li 2.95 K 0.05 )YCl 3 Br 3 The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 3. From the results in Figure 3, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 2.0×10 at 25°C. -3 It was S / cm.
[0069] <Example 8> A solid electrolyte material was prepared using the same method as in Example 1. The target composition was (Li 2.9 K 0.1 )YCl 3 Br 3 The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 3. From the results in Figure 3, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 1.7 × 10 at 25 °C. -3 It was S / cm.
[0070] <Comparative Example 1> A solid electrolyte material was prepared using the same method as in Example 1. The target composition was Li 3 Y.C.L. 3 Br 3 The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 2. From the results in Figure 2, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 1.5×10 at 25°C. -3 It was S / cm.
[0071] <Comparative Example 2> A solid electrolyte material was prepared using the same method as in Example 1. The target composition was Li 2.6 Na 0.4 Y.C.L. 3 Br 3 The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 2. From the results in Figure 2, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 9.4 × 10 at 25 °C. -4 It was S / cm.
[0072] <Comparative Example 3> A solid electrolyte material was prepared using the same method as in Example 1. The target composition was Li 2.4 Na 0.6 Y.C.L. 3 Br 3 The X-ray powder diffraction pattern measured for this solid electrolyte material is shown in Figure 2. From the results in Figure 2, it was confirmed that halide crystals with the target composition were produced. The ionic conductivity of the obtained solid electrolyte material was 1.5×10 at 25°C. -4 It was S / cm.
[0073] The above results are summarized in Table 1 below.
[0074] [Table 1]
[0075] From the results in Table 1, in Examples 1 to 8, which contain an alkali metal element other than lithium in addition to lithium, yttrium, and a halogen element, and have a cation ratio of more than 0 and 0.07 or less, the cation ratio of 1.6 × 10 is the borderline for practical use. -3 It was confirmed that the ionic conductivity of the material exceeded that of the conventional material. On the other hand, in Comparative Example 1, which does not contain any alkali metal elements other than lithium, even when prepared in the same manner as in the Examples, the ionic conductivity was still 1.6 × 10 -3 It was found that the rate of decline was below 10%.
[0076] From these results, it was found that in a solid electrolyte material that does not contain sulfur but contains a halogen element, if the solid electrolyte material contains lithium element, yttrium element, and an alkali metal element other than lithium element, the ionic conductivity can be improved.
[0077] Although this is not shown as an example due to cost considerations, it can be reasonably assumed that similar results to those in these examples would be obtained even if only chlorine atoms or bromine atoms were used as the M2 element. [Explanation of symbols]
[0078] 1. All-solid-state lithium-ion secondary battery 10 Positive electrode layer 20...Negative electrode layer 30...Solid electrolyte layer
Claims
1. A solid electrolyte material is a compound represented by the following general formula (Chemical Formula 1): a cation ratio (M1 / Li+M1), which is the content ratio of the M1 element to the total amount of the lithium element and the M1 element in the general formula (Chemical Formula 1), is greater than 0 and is 0.07 or less; A solid electrolyte material characterized by having peaks at least at 2θ=27.72°±0.50°, 31.9°±0.50°, 46.34°±0.50°, 55.19°±0.50°, and 57.39°±0.50° in X-ray diffraction measurement using CuKα radiation. 【Chemistry 1】 (In the formula, the M1 element includes at least one selected from the group consisting of Na, K, Rb, Cs, and Fr. The M2 element includes at least one selected from the group consisting of Cl, Br, I, and F. In the formula, x is greater than 0 and less than 3.)
2. The solid electrolyte material according to claim 1 , wherein the value of x in the formula is greater than 0 and less than or equal to 0.
21.
3. The solid electrolyte material according to claim 1 or 2, wherein the M1 element is Na and / or K.
4. The solid electrolyte material according to claim 1 , wherein the M2 element is Cl and / or Br.
5. The solid electrolyte material according to claim 4, wherein the M2 element is Cl and Br.
6. A solid electrolyte comprising the solid electrolyte material according to claim 1 .
7. An all-solid-state secondary battery comprising the solid electrolyte according to claim 6.
8. A step of mechanically milling a mixture of LiM2, YM2 and M1M2 in a predetermined ratio to obtain glass; and heat-treating the glass at a temperature equal to or higher than the glass transition temperature to obtain a glass ceramic having a composition represented by the following general formula (Chemical formula 2), in which a cation ratio (M1 / Li+M1), which is the content ratio of the M1 element to the total amount of the lithium element and the M1 element in the general formula (Chemical formula 2), is greater than 0 and is 0.07 or less. 【Chemistry 2】 (The M1 element in the formula includes at least one selected from the group consisting of Na, K, Rb, Cs, and Fr. The M2 element in the formula includes at least one selected from the group consisting of Cl, Br, I, and F. x in the formula is greater than 0 and less than 3.)
Citation Information
Patent Citations
Solid electrolyte material and battery using the same
JP2020109047A
Solid electrolyte material, and cell
WO2018025582A1
Electrolyte material and methods of forming
WO2022032311A1